DISTRIBUTION PATTERNS AND SETTLEMENT DENSITY USING NEAREST NEIGHBOR ANALYSIS AND KERNEL DENSITY ANALYSIS IN DIY COASTAL AREAS - Yusliana Yusliana; Lulu Mari Fitria; Emilius Paldi Antus; Irsyad Adhi Waskita Hutama (JURNAL GEOGRAFI, 2022)
DIY's coastal area is one of DIY's development priorities by establishing the site as an economic corridor that impacts physical development, such as settlements in the coastal area of DIY. This study aims to analyze the distribution and density of settlements. The method used in research is a quantitative descriptive and Geography Information System approach. The analysis used in this study is Nearest Neighbour Analysis (NNA) and Kernel Density Analysis with an analysis tool in ArcGIS 10.5. The results of the NNA show that the three districts located on the coast of DIY have the same distribution pattern characteristics, namely, the clustered pattern, which means the NNA index value is <1 or the T value ranges from 0-0.80. The results of the kernel density analysis show that the most significant density is found in Kulon Progo Regency, precisely in Wates District, and Bantul Regency, precisely in Srandakan District. At the same time, for Gunung Kidul Regency, it is less significant, and the density is only centered on one density point. Several factors cause settlement density, including physical factors (topography, slope, soil type, and clean water sources), accessibility (proximity to transportation routes and proximity to the city center), availability of facilities and infrastructure (electricity network, educational facilities, and health), and environmental factors (natural and human resources).Keywords: Settlements, Coastal, NNA, Kernel Density